ICT AND EMPLOYMENT PROMOTION AMONG POOR WOMEN: HOW CAN WE MAKE IT HAPPEN? SOME REFLECTIONS ON KERALA'S EXPERIENCE - P. Mohanan Pillai N. Shanta (Centre for Development Studies-WP398, 2008)
This paper deals with the integration of gender in policies relating to information and communication technology to empower socially excluded poor women as producers of this technology. In this context, this paper examines an interventionist ICT policy undertaken by Kudumbasree (an innovative women based participatory programme)to empower poor women .The central part of the investigation is a survey of Kudumbasree supported micro enterprises scattered across the state to understand the nature and characteristics of the enterprises, activity pattern and performance parameters. The analysis of the paper is divided into two parts. First part deals with the structure and performance of women led enterprises and the second deals with issues relating to women, work and welfare. From the evidence gathered, we can conclude that the ICT initiatives under the umbrella of Kudumbasree have vast potential forempowering the poor women. The study clearly establishes that given the basic literacy of the state, engendering ICT for poor women is feasible, provided the right organisational support is given. Poor women through this programme have entered the lowest of IT enabled jobs. If this good beginning has to be sustained and poor women have to take advantage of the opportunities offered by the IT revolution, they should be helped to move to higher levels of activities with more intense training and organisational support. There is a need for continuous upgradation of skills and capacity building particularly in the context of the fast changing technology associated with the IT sector. The point that needs to be stressed is that while the agency hasconcentrated on the supply side, the demand side aspects such as output demand, market research, customer service etc; have been largely ignored. For best results the supply and demand factors need to be tackled in an integrated manner. The current practice of digitization of government records through Kudumbasree has its limitations. Work is 5 bound to peter out when the backlog of digitization work is completed. The solution to this lies in the expanded role of the agency. The units have to diversify the customer base with government acting as a facilitator. Maybe the government can set up a flexible independen t apex body, or alternatively an alliance of units to strengthen their bargaining power. To conclude, although we cannot expect with the given levels of education, for the women to move to very high levels of work like software development it is possible to ensure continuous income and employment through work contracts of a different nature-work of a continuous nature and not programme specific like electronic publishing, customer call centres, records management etc. which will fall well within their educational capabilities. ICT is certainly a promising sector for theempowerment of poor women and for them to become partners in development